Coastal environments and long-term human practices in Corfu: a seascape perspective - Sbonias, Kostas (Journal of Greek Archaeology, 2022)
Seascapes, both as specific ecosystems and as cultural manifestations formed through human action, are important in shaping economic and social relations and entail a range of experiences and meanings for human societies. Several studies in recent decades have underlined the importance of island environments and seascapes. The factors that shape the dynamic relationship with the sea and form its cultural expression, as well as the resources and activities related to it and the way they are perceived and change over time are important parameters in approaching seascapes. The investigation of the coastal environment of Corfu through a diachronic perspective using a variety of sources, such as archaeological remains, ethnographic evidence and archival material, was developed in the framework of the Fish&CHIPS project. The project aimed to link the historical and archaeological research of the coastal environment as a special ecosystem and part of the cultural heritage, at the regional level, with the current fishing communities of Corfu and Taranto in Apulia. It also aimed to highlight the interconnection of human societies, from ancient times to the present, with the sea and its resources, focusing on fishing and maritime traditions, and at a second level to contribute to the creation of sustainable development prospects for the local fishing communities through the diversification of their economic activities. The present paper focuses on key aspects of the marine and coastal environment of Corfu and the way it was transformed over time. The starting point is the strategic location of Corfu in the seascape of the Ionian and Adriatic Seas and the coastal ecosystems that form part of the island’s landscape (coastal and inland villages related to the sea, wetlands and lagoons, estuaries, salt flats). They are considered primarily in economic terms, examining resources and practices of exploitation of these environments in different periods and, also, influences on patterns of habitation and landscape use. The Community Map of Southern Corfu was developed on the basis of research into these environments in both spatial and temporal aspects and in cooperation with the present-day local communities (Figure 1). The aim was to increase the value of the coastal and marine environments as part of the cultural heritage of the region and create a network of walking cultural routes that link these specific environments and their communities and form the core of the ‘Petritis and South Corfu Ecomuseum’. The ecomuseum approach moves beyond the closed walls of conventional museums and its basic principles can be summarised as follows: a) the importance of the wider geographical region and its perception by the local communities through the experiences and traditions that shape the collective memory and identity of an area, b) the promotion and on-site preservation of elements of the material and intangible heritage resources of the place, c) the active participation of the local community and d) a direction towards sustainability and regeneration, with a parallel connection with primary production (crafts, arts and crafts, ecotourism facilities, cultural tourism).